THE EMPOWERMENT OF CADRES AND TRADITIONAL BIRTH ATTENDANTS IN THE EARLY DETECTION AND PREVENTION OF STUNTING IN NORTH BOGOR DISTRICT, BOGOR, WEST JAVA - Evi Martha; Nindy Audia Nadira; Trini Sudiarti; Aisyah Putri Mayangsari; Embun Ferdina Enjaini; Tika Puspa Ryanthi; Dina Evariyana Bangun (Universitas Airlangga, 2020)
Stunting associated to the increased risk of morbidity and mortality, reduced physical capacity, impaired development and function of children’s motor and mental condition. Efforts have been made by the Government through Integrated Healthcare Center (IHC), however it is less optimal as it didn’t involved all aspects of the community. Cadres and TBAs are important parts of the community that are strategic enough to be involved in this activity, because they are very close to mothers and the community.This program aims to improve the knowledge and practice of 31 cadres and traditional birth attendants (TBA) in early detection and prevention of stunting and implement their knowledge to the community by using lecture, discussion, practice, and film screening methods. There is a significant difference in the knowledge level of cadres and TBA between pre and post training (p value = 0.0005) with knowledge improvement of 30.68%. Furthermore, cadre and TBA did a Follow-Up Plan (FUP) in the form of stunting socialization and education, particularly to the expectants and mothers, with the results of about 124 people exposed to stunting. To monitor FUP, team formed a total of 3 Whatsapp Groups for each village as a forum of communication and discussion between fellow participants to PHC and Research Team. As the result, almost all trainees informed the FUP through Whatsapp group, in the form of socialization and education to other cadres and mothers during IHC, recitations, village activities, sports activities, as well as family or neighbors individually, etc. Through the empowerment of cadres and TBA, education on early detection and prevention of stunting goes according to expectations and is quite effective to the role of cadres and TBA in the community.Keywords: stunting, cadre, traditional birth attendant, empowerment